IMPLEMENTASI PERHITUNGAN PAJAK PERTAMBAHAN NILAI ATAS TRANSAKSI REKANAN PADA COFFEE 36 KAB. GOWA - Muryani Arsal; Andi Arifwangsa Adinigrat; A.Baso Kumala Putra (Jurnal Riset Perpajakan: Amnesty, 2021)
The purpose of this study was to determine how the implementation of value added tax calculations on counterparty transactions at Coffee 36 Kab. Gowa. This type of research is descriptive quantitative research. Data collection techniques using literature study, observation, interviews and documentation. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results showed that the Implementation of VAT Calculation on Partner Transactions at Coffee 36 Kab. Gowa is only subject to VAT, namely Input Tax on the purchase of raw materials from its partners and the VAT collected should not be tax but service charge or commonly called service fee.